Early Ditection of Central Nervous System Infection by C-reactive Protein Examination of Cerebrospinal Fluid - Tjipta Bahtera; Bagus Putu Ngurah Arsana; Maria Lidwina (Paediatrica Indonesiana, 1992)
There are still many cases of bacterial meningitis in Indonesia. The highest morbidity rate are between 2 months until 2 years of age. The important factors that influence the success of treatment are early diagnosis and detection of the cause. C-reactive protein (=CRP) could be found in the spinal fluid of meningitis patients. The aim of this study is to judge the ability of CRP as a tool in making diagnosis as soon as possible whether there is a bacterial infection of the central nervous system and to compare it with the result of the spinal fluid culture. Also to compare the ability of it a conventional or routine examination of the spinal fluid was done. This was a prospective study on 30 children that were admitted in the child ward of Kariadi Hospital, Semarang during the first of April until the and of july 1990. The ages of the children were between one month until 14 years, with clinical symptoms such as fever, seizure and neurological disorders. CRP examination was done with Latex Agglutination method. The result of CRP examination on spinal fluid showed that the sensitivity was 91.6% , the specificity 94.4% , the positive prediction value 91.6% and the negative prediction value 94.4%. As a conclusion, CRP examination of spinal fluid gives better results than the conventional or routine examination in distinguishing bacterial meningitis from non bacterial meningitis.